Management of anxiety using eye movement desensitization and reprocessing therapy in children undergoing extraction: a randomized controlled pilot study - Kalra, Namita; Rathore, Apoorva; Tyagi, Rishi; Khatri, Amit; Khandelwal, Deepak; Yangdol, Padma (Journal of Dental Anesthesia and Pain Medicine, 2023)
Eye movement desensitization and reprocessing (EMDR) therapy has been reported to be very efficacious for treating post-traumatic stress disorder (PTSD) and other anxiety-related conditions. However, a review of the literature reveals the sparse use of this therapy in the field of pediatric dentistry. This study aimed to evaluate anxiety trends in pediatric dental patients during local anesthesia and extraction with and without EMDR therapy. Children in the age range of 8-12 years who required dental extractions were assigned randomly into two groups: an EMDR group (group 1) and a routine behavior management therapy group (group 2; receiving more traditional interventions such as tender love and care behavioral modeling, and distraction). Anxiety scores were recorded at four levels using the visual facial anxiety scale (VFAS) preoperatively, after therapy, after the administration of local anesthesia (LA), and after extraction. Reduced anxiety was observed after the delivery of EMDR therapy, after LA administration, and post-extraction in the EMDR group compared to pre-operative anxiety scores of anxiety (P < 0.001; unpaired Student's t and Mann-Whitney U tests). In the control group, mild reductions in anxiety after routine behavior management therapy were observed, accompanied by spikes in anxiety levels after LA and extractions. EMDR therapy was found to be valuable for reducing anxiety among pediatric dental patients during tooth extraction procedures.